Inspiratory pressure maximum and its relationship with symptoms and factors associated with reflux disease gastroesophageal - Ezana Sandrina Almada Fernandes de Borja (2015)
The gastroesophageal reflux disease is the return of gastric contents through the lower esophageal sphincter regardless of etiology, manifesting itself by symptoms (typical or atypical) or tissue damage. The diaphragm is the main respiratory muscle and its crural part one of the fundamental components of the antireflux barrier. Contractions of this are related to changes in pressure of the gastroesophageal junction that are usually related to breathing. Studies show evidence of diaphragmatic weakness in gastroesophageal reflux disease that can be improved with diaphragmatic training. The maximal inspiratory pressure is a simple method to evaluate the inspiratory force determined by diaphragm. From this context, the hypothesis that the symptoms of gastroesophageal reflux disease may be associated with the maximal inspiratory pressure. Objective: to measure maximal inspiratory pressure and relate it to the symptoms and factors associated with gastroesophageal reflux disease. Methodology: it is a cross-sectional study in humans, where 404 patients were recruited in accordance with the inclusion and exclusion criteria. They underwent a clinical evaluation, measurement of maximal inspiratory pressure and upper endoscopy. Results: We studied 269 women and 135 men, mean age 44.4 Â 13.7 years and 40.4 Â 13.3 years for patients with and without deficit of maximal inspiratory pressure respectively. The weight averaged 72.4 Â 21.8 kg for patients without deficit of maximal inspiratory pressure, and 66.4 Â 15.5 kg for patients with deficit of maximal inspiratory pressure. In relation to the average height was 161 Â 0.9 cm for patients without deficit of maximal inspiratory pressure and 157 Â 0.1 cm for patients with a deficit of maximal inspiratory pressure. This difference was statistically significant for age, weight and height respectively (p=0.005, p=0.002, p=0.0293). The mean maximal inspiratory pressure was 69.2 Â 22.8 cm H2O, with 210 (51.98%) patients had a deficit of maximal inspiratory pressure. Two hundred and sixty-six (65.8%) patients had comorbidities. Sixty-seven (16.6%) patients had erosive esophagitis. There was statistical significance in the prediction of deficit of maximal inspiratory pressure from symptoms of dysphagia and excess mucus in the throat or nose, with p=0.0357 and p=0.0207, respectively. On the other hand, there was no statistical significance when the variable considered was esophagitis (p=0.38). Females have higher scores to the scores Reflux Disease Questionnaire (p=0.006) and Reflux Symptoms Index (p=0.001), with statistical significance. Conclusions: maximal inspiratory pressure was influenced by the age, weight and height significantly; there was no association of maximal inspiratory pressure deficit with esophagitis; heartburn and regurgitation had no association with deficit of maximal inspiratory pressure; some atypical symptoms such as dysphagia and excess mucus in the throat or nose showed a statistically significant relationship with the deficit of maximal inspiratory pressure; there was no association of maximal inspiratory pressure deficit with direct related symptoms or indirectly to the upper gastrointestinal tract.